Re-employment Dynamics of Disabled Workers - Hielke Buddelmeyer (Institute for the Study of Labor (IZA), 2001)
We investigate the duration of time until the first work resumption for a cohort of people who receive disability insurance benefits. One of the peculiarities of the disability insurance program under investigation is that the level of benefits not only depends on previous wages, but also declines over time according to a schedule based on age, the amount of work experience, and the level of disability. As a result, different people will face different benefit schedules and hence are likely to make different choices regarding a return to work. To fully absorb the structural aspect of the disability program, we specify and estimate a behavioral labor supply model where individuals receive job offers that they can accept or decline. Possible reforms of the disability program are evaluated, including ending the disability program altogether.
Keywords: J22; J64; C41; 330; Disability; labour supply; behavioural modeling; Behindertenpolitik; Erwerbsunfähigkeitsrente; Wirtschaftspolitische Wirkungsanalyse; Behinderte; Arbeitsangebot; Erwerbsunfähigkeit; Schätzung; Niederlande